(untitled) (BIBECHANA, 2012)
The histomorphology and gonadial cycle of a freshwater garfish Xenentoton cancila revealed that the ovaries of the fish pass through resting, early maturing advanced maturing, pre-spawning, spawning and spent phases within one year. The oogenetic activity starts in November and continues upto June(GSI=10.19)-July(GSI=11.38), when ovaries are full of yolky eggs. Only young oogonia and oocytes l appeared in September to October. The oocytes of l,ll,lll,lV and V stages were present during November to February. The oocytes Vl and Vll were seen dominated by ripe oocytes during June to late July when spawning takes place. Asychronism mode of oocyte development was recorded in X.cancila. Keywords: Xenentodon cancila; oocyte development; reproductive cycle; spawning DOI: http://dx.doi.org/10.3126/bibechana.v8i0.5694 BIBECHANA 8 (2012) 96-104